Arbitration Law- A Primer - Taly, Mallika (Eastern Book Company, 2011)
Since arbitration is a cost effective and quick way of settling disputes and has become a preferred alternative to the courts, its understanding is necessary for all entrepreneurs, managers, students, academicians, in addition to judges and lawyers. This book meets this requirement and provides the necessary introduction to Arbitration law in a simple and concise way.